2015
DOI: 10.1109/tasc.2014.2378993
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Phase Purity of CSD Bi-2223 Thin Films Through Protected Sintering Method

Abstract: Pure Bi 2 Sr 2 Ca 2 Cu 3 O x (Bi-2223) phase is hard to be achieved in Bi-2223 thin films fabricated by using chemical solution deposition (CSD) due to the volatilization of specific elements. Two protected sintering methods were proposed in this work to enhance the phase purity of CSD Bi-2223 thin films. One method is two deposited thin films stacked "face-to-face" (FTF) and then sintered. A "substrate/precursor film/precursor film/substrate" architecture was used during sintering instead of common "precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…This study demonstrated the feasibility of (Bi, Pb)-2223 thin films with a considerable J c property being obtained via CSD. Compared to our previous study [28] in which J c was zero, the reason for the improvement in this study can mainly be attributed to the favorable biaxial texture caused by the epitaxial growth, as shown in figures 7 and 8. The a-axial lattice of the LAO substrate (a LAO ) is 0.3789 nm (PDF#850848), while the a-axial and b-axial lattices of (Bi, Pb)-2223 (a 2223 and b 2223 ) are 0.5399 nm and 0.5413 nm (PDF#460745), respectively.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…This study demonstrated the feasibility of (Bi, Pb)-2223 thin films with a considerable J c property being obtained via CSD. Compared to our previous study [28] in which J c was zero, the reason for the improvement in this study can mainly be attributed to the favorable biaxial texture caused by the epitaxial growth, as shown in figures 7 and 8. The a-axial lattice of the LAO substrate (a LAO ) is 0.3789 nm (PDF#850848), while the a-axial and b-axial lattices of (Bi, Pb)-2223 (a 2223 and b 2223 ) are 0.5399 nm and 0.5413 nm (PDF#460745), respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…The FTF structure together with 0.7 g powder of Pb 0.33 Bi 1.80 Sr 1.87 Ca 2.00 Cu 3.00 O x were wrapped in 0.1 mm thick silver foil and sealed by using silver paste. Such a PIF process could help to reduce the evaporation of elements during sintering and improve the quality of the (Bi, Pb)-2223 thin films, as reported in our previous publication [28]. The sealed samples were sintered in 8 vol.% O 2 (N 2 balanced) with a heating rate of 200 °C h −1 and a dwelling at various sintering temperatures (T S ) for 10 h.…”
Section: Sample Fabricationmentioning
confidence: 98%
See 2 more Smart Citations